2021
DOI: 10.3390/wevj12040239
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Improvement Measures of Driving Range Attenuation of Electric Vehicles in Winter

Abstract: A great many EVs in cold areas suffer from range attenuation in winter, which causes driver anxiety concerning the driving range, representing a hot topic. Many researchers have analyzed the reasons for range attenuation but the coupling mechanism of the battery as well as the vehicle and driving conditions have not been clearly estimated. To quantitatively investigate the driving range attenuation of electric vehicles (EVs) during winter, an EV model mainly integrated with a passenger-cabin thermal model, bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Nevertheless, LIB suffer from a serious energy attenuation problem in low temperature, especially LFP batteries [7,8]. Qin et al reviewed the performance of batteries at low temperature and illustrated that the discharge capacity of LFP drops from 134.5 mAh/g (20 • C) to 90 mAh/g (−20 • C) [9], which corresponds to the authors' pre-experiment, as shown in Supplementary Material Figure S1.…”
Section: Introduction 1backgroundsmentioning
confidence: 85%
See 3 more Smart Citations
“…Nevertheless, LIB suffer from a serious energy attenuation problem in low temperature, especially LFP batteries [7,8]. Qin et al reviewed the performance of batteries at low temperature and illustrated that the discharge capacity of LFP drops from 134.5 mAh/g (20 • C) to 90 mAh/g (−20 • C) [9], which corresponds to the authors' pre-experiment, as shown in Supplementary Material Figure S1.…”
Section: Introduction 1backgroundsmentioning
confidence: 85%
“…In this study, a two-state lumped parameter thermal model is constructed as the single cell model, the EKF algorithm is introduced as the closed-loop method to estimate the battery core temperature, and a network of single cells is connected to form the module model. The modeling is based on the battery pack of Wuling HongGuang Mini EV (SAIC GM Wuling Automobile Co., Ltd., Liuzhou, China) [8].…”
Section: Battery Thermal Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…[19] The 37.27% power loss of electric vehicles by using air-conditioning has also been reported. [20] The VIPV is thought to be useful for heat shielding.…”
Section: Effects Of Usage Of Air Conditioner Upon Driving Distance Of...mentioning
confidence: 99%